2006
DOI: 10.1021/ol0614121
|View full text |Cite
|
Sign up to set email alerts
|

A Dibenzofuran-Based Host Material for Blue Electrophosphorescence

Abstract: Dibenzofuran (DBF) is converted to a vacuum-sublimable, electron-transporting host material via 2,8-substitution with diphenylphosphine oxide moieties. Close pi-pi stacking and the inductive influence of P=O moieties impart favorable electron-transport properties without lowering the triplet energy. A maximum external quantum efficiency of 10.1% and luminance power efficiency of 25.9 lm/W are realized using this material as the host for the blue-green electrophosphorescent molecule, iridium(III) bis(4,6-(di-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(151 citation statements)
references
References 11 publications
3
145
0
2
Order By: Relevance
“…The operating voltages of A and B were much lower than those of FIrpic-based PHOLEDs with p-DBFDPO as the host, for which 800 cd cm À2 can be achieved at 5.4 V. [33] This also demonstrates the stronger carrier injection ability of o-DBFDPO relative to p-DBFDPO, which can be attributed to the stronger polarisation effect of short-axis substitution and further confirms the conclusions of optical and theoretical calculation analysis. It was shown that devices A and B have almost identical brightness/voltage (B/V) characteristics.…”
Section: à2supporting
confidence: 78%
See 2 more Smart Citations
“…The operating voltages of A and B were much lower than those of FIrpic-based PHOLEDs with p-DBFDPO as the host, for which 800 cd cm À2 can be achieved at 5.4 V. [33] This also demonstrates the stronger carrier injection ability of o-DBFDPO relative to p-DBFDPO, which can be attributed to the stronger polarisation effect of short-axis substitution and further confirms the conclusions of optical and theoretical calculation analysis. It was shown that devices A and B have almost identical brightness/voltage (B/V) characteristics.…”
Section: à2supporting
confidence: 78%
“…DSC analysis shows that the melting point (T m ) of o-DBFDPO is 356 8C (Figure S1, inset in the Supporting Information), which is nearly 170 8C higher than that of o-DBFDPO and attributable to the enhanced p-p intermolecular interaction. Significantly, the glass transition temperature (T g ) of o-DBFDPO is as high as 191 8C, about 100 and 90 8C higher than those of o-DBFPPO [43] and p-DBFDPO, [33] respectively, and is outstanding among the small molecular hosts. Obviously, the symmetrical structure of o-DBFDPO greatly improves the thermal performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Phosphine oxide-based electron transport materials have also been reported and triphenylphosphine oxide has been used as an electron transport material and found to decrease the driving voltage of OLEDs. 8,9 Spiro-type derivatives containing fluorene and benzofluorene have received a great deal of attention as fluorescent materials for OLEDs, because asymmetrical spiro compounds having naphthalene groups can not only preserve their inherent characteristics, such as their morphological stability, high glass transition temperature and amorphous properties, but also provide a variety of substituents on the aromatic ring of the spiro molecules, resulting in the formation of conjugation controlled OLED host and dopant materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the neighboring hole-and electron-transporting materials should have higher TE than that of the blue phosphor [6] to prevent the triplet exciton quenching. However, these kinds of materials are rare and hard to design [7,8]. Based on a conventional blue phosphorescent dopant and their host materials, a common approach of improving the performance is to optimize the emitting layer (EML), such as introduction of a mixed-host architecture [9,10], double hosts [11], and stepwise EML [12][13][14][15][16], and so on.…”
mentioning
confidence: 99%